2022
DOI: 10.2147/prbm.s371092
|View full text |Cite
|
Sign up to set email alerts
|

How Classroom Environment Influences Academic Enjoyment in Mathematics Among Chinese Middle School Students: Moderated Mediation Effect of Academic Self-Concept and Academic Achievement

Abstract: Purpose Substantial literature has documented the influence of classroom environment on academic enjoyment. However, little is known about the mediating and moderating mechanisms underlying this relationship. Based on the control-value theory and the individual-context interaction model, a moderated mediation model was constructed in this study to further examine whether academic self-concept mediated the relation between classroom environment and enjoyment in mathematics and whether this mediatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Many research frameworks have been built on mathematical beliefs (Hannula, 2011(Hannula, , 2012. The teaching beliefs of mathematics teachers refer to their orientations toward teaching mathematics, which involve perspectives regarding instructional activities, the cognitive processes of students, and the purpose of mathematics (Wang et al, 2022). Currently, the transmissive and constructive taxonomy of teaching beliefs is commonly used in existing studies and international assessments, such as TEDS-M (Blömeke and Kaiser, 2014).…”
Section: Research Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many research frameworks have been built on mathematical beliefs (Hannula, 2011(Hannula, , 2012. The teaching beliefs of mathematics teachers refer to their orientations toward teaching mathematics, which involve perspectives regarding instructional activities, the cognitive processes of students, and the purpose of mathematics (Wang et al, 2022). Currently, the transmissive and constructive taxonomy of teaching beliefs is commonly used in existing studies and international assessments, such as TEDS-M (Blömeke and Kaiser, 2014).…”
Section: Research Toolsmentioning
confidence: 99%
“…As research in mathematics education continues to evolve, the mathematics classroom has gradually become the focus of research. Focusing on the role and functions of mathematics teachers in the classroom , on what happens in the classroom , and on the influence of the classroom environment on students' interest in learning (Liu et al, 2022) are all important for academic research. As an essential part of the mathematics classroom, teachers play a significant role in imparting knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…They are emotional connections that are established through specific activities among students in a learning environment [78]. The academic community generally defines the relationships between classmates as the care, support, and overall interactions experienced by students in the classroom [79]. Research has found that classmate relationships have certain effects on students' psychosocial development, engagement in learning, and academic achievement [80,81].…”
Section: The Mediating Role Of Classmate Relationshipsmentioning
confidence: 99%
“…Second, our study only demonstrated the stability of the twofold multidimensional structure of ASC with Chinese secondary school students, future research should extend such longitudinal investigation into Chinese students of other age groups and students in other cultures. Another limitation is that our study did not include other important factors in learning, such as learning engagement (Henning et al, 2022), academic enjoyment (Liu et al, 2022), study interest (Fryer and Ainley, 2019), and achievement emotions (Forsblom et al, 2022). Including these important elements may help reveal complex relations (e.g., mediating relations) between ASC, learning outcomes, and these factors.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%